Inter-area Oscillation Damping using an STATCOM based Hybrid Shunt Compensation Scheme - Vahid Farzam; Ahad Mokhtarpour (Institute of Advanced Engineering and Science, 2016)
FACTS devices are one of the latest technologies which have been used to improve power system dynamic and stability during recent years. However, widespread adoption of this technology has been hampered by high cost and reliability concerns. In this paper an economical phase imbalanced shunt reactive compensation concept has been introduced and its ability for power system dynamic enhancement and inter-area oscillation damping are investigated. A hybrid phase imbalanced scheme is a shunt capacitive compensation scheme, where two phases are compensated by fixed shunt capacitor (C) and the third phase is compensated by a Static Synchronous Compensator (STATCOM) in shunt with a fixed capacitor (CC). The power system dynamic stability enhancement would be achieved by adding a conventional Wide Area Damping Controller (WADC) to the main control loop of the single phase STATCOM. Two different control methodologies are proposed: a non-optimized conventional damping controller and a conventional damping controller with optomised parameters that are added to the main control loop of the unbalanced compensator in order to damp the inter area oscillations. The proposed arrangement would, certainly, be economically attractive when compared with a full three-phase STATCOM. The proposed scheme is prosperously applied in a 13-bus six-machine test system and various case studies are conducted to demonstrate its ability in damping inter-area oscillations and power system dynamic enhancement.